2014
DOI: 10.6028/nist.tn.1844
|View full text |Cite
|
Sign up to set email alerts
|

Potential Research Areas in Residential Energy Storage for NIST’s Engineering Laboratory

Abstract: This paper recommends research that is required to develop and, thus, enable cost effective, residential electricity storage systems for renewable energy. As residential electricity generation from renewable sources becomes more prevalent, residential energy storage will become an important factor in ensuring the stability of the electrical grid; grid operators will be able to timeshift demand to smooth peaks and match supply capacity. However, local storage of excess energy from renewable sources is currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A PCM with low vapor pressure and that was immiscible with R134a (and presumably R410A) was identified. Kedzierski et al (2014) identified a remote/discrete PCM design for PCM storage with a residential ASHP. The purpose of the present investigation is to design a DCHEX for discrete PCM energy storage for use in air conditioning NIST's NZERTF.…”
Section: Introductionmentioning
confidence: 99%
“…A PCM with low vapor pressure and that was immiscible with R134a (and presumably R410A) was identified. Kedzierski et al (2014) identified a remote/discrete PCM design for PCM storage with a residential ASHP. The purpose of the present investigation is to design a DCHEX for discrete PCM energy storage for use in air conditioning NIST's NZERTF.…”
Section: Introductionmentioning
confidence: 99%